Prediction of water erosion in the Sumidero Canyon basin, Chiapas - Torres Benites, Elibeth; Cortes Becerra, José; Uresti Gil, Jesús; Torres Cedillo, Luis; Rivera Torres, Pedro Sinai (Revista Mexicana de Ciencias Agrícolas, 2020)
In the Sumidero Canyon Basin, Chiapas state, Mexico, the soil is a component of the natural environment strongly affected by erosion due to inadequate management of the soil resource. Measuring soil erosion is time consuming and data on soil erosion rates in Mexico are limited and punctual and provide little information on soil loss rates at the basin level. In the present study, methodologies were used for the application of the USLE/RUSLE, developed in various studies and countries, in order to carry out the cartography of water erosion of the Sumidero Canyon Basin, which constitutes a significant tool for making decisions. in the management and conservation of soils. A series of methodological tools is proposed for the generation of the water erosion cartography using information in Mexico at various scales. The results are presented as an average annual geographic reference of soil loss and its monthly distribution. The analysis of results indicates that 73% of the basin presents some degree of erosion, that June is the month that erosion is greatest (7 021 906.9 t) and that the average annual erosion in the study area is 41.5 t ha-1 year-1.
Keywords: GIS; natural resources; RUSLE; USLE